Deep Brain Stimulation of the Pallidum is Effective and Might Stabilize Striatal D2 Receptor Binding in Myoclonus–Dystonia - Beukers, Richard J.; Contarino, Maria F.; Speelman, Hans D.; Schuurman, P. R.; Booij, Jan; Tijssen, Marina A. (Frontiers in Neurology, 2012)
Purpose: To assess clinical efficacy of deep brain stimulation of the pallidum in Myoclonus-Dystonia patients, and to compare pre- and postoperative striatal dopamine D2 receptor availability. Methods: Clinical parameters were scored using validated rating scales for myoclonus and dystonia. Dopamine D2 receptor binding of three patients was studied before surgery and approximately two years post-operatively using 123I-iodobenzamide Single Photon Emission Computed Tomography. Two patients who did not undergo surgery served as controls. Results: Clinically, the 3 Myoclonus-Dystonia patients improved 83%, 17% and 100%, respectively on the myoclonus rating scale and 78%, 23% and 65% on the dystonia rating scale after deep brain stimulation. Dopamine D2 receptor binding did not change after surgery. In the two control subjects, binding has lowered further. Conclusions: These findings confirm that deep brain stimulation of the pallidum has beneficial effects on motor symptoms in Myoclonus-Dystonia and suggest this procedure might stabilize dopamine D2 receptor binding.